Long-Term Cognitive and Functional Outcomes of Anesthesia and Surgery in Patients with Dementia - Antea Krsek; Lana Sabati; Ivana Krajina; Zofia Nikola Lewandowska; Vlatka Sotosek; Lara Baticic (Healthcare, 2026)
Dementia is one of the leading causes of disability and dependence among older adults and is increasingly encountered in patients undergoing surgery. As populations age and surgical interventions become more common, understanding the perioperative care of patients with pre-existing dementia has become an important clinical priority. Dementia is associated with reduced cognitive reserve, chronic neuroinflammation, synaptic dysfunction, blood–brain barrier impairment, neurotransmitter abnormalities, and cerebrovascular dysregulation, all of which may increase vulnerability to perioperative neurological injury. Surgical trauma and anaesthesia trigger systemic inflammatory, metabolic, and haemodynamic responses that may disrupt cerebral homeostasis and contribute to perioperative neurocognitive disorders, including postoperative delirium and delayed neurocognitive recovery. Postoperative delirium is consistently associated with accelerated cognitive and functional decline and may represent an important link between perioperative stress and adverse long-term outcomes. However, despite strong biological plausibility, current clinical evidence does not establish a direct causal relationship between anaesthesia, surgery, and accelerated dementia progression. Interpretation of the available literature is limited by methodological heterogeneity, residual confounding, and the frequent exclusion of patients with established cognitive impairment. This narrative review summarizes the neurobiological mechanisms underlying increased perioperative vulnerability in dementia, critically examines current evidence regarding the effects of anaesthesia and surgery on long-term cognitive and functional outcomes, and discusses practical strategies to reduce perioperative risk. A better understanding of these complex interactions is essential to optimize perioperative care and preserve cognitive function, functional independence, and quality of life in this highly vulnerable patient population.